LOYALITAS PELANGGAN KUNCI SUKSES SEORANG PENGUSAHA - Sugiantono A. R. (STIE Mandala Jember, 2014)
There is no one company was successful in a few months or even years, with no cause /issue nothing, then stop in the middle of the street where his business in a state of good repair company. To exist among the people is not easy, companies must be smart in order to keep their customers not to switch to other similiar companies. Competition is getting tougher and increasingly fierce, every company is required to have its own strategy in a harmonious relationship between the company and its customers. Harmonious relationship between the customer and the company, the customer can be called true or loyal customer. If the company can build its customers, so that customers can be loyal or called customer loyalty, then certainly that the entrepreneur will be successful in doing business.